Primary culprit for tooth loss!! - Sailavanya Nuvvula; Vijay Kumar Chava; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2016)
Aim: In order to facilitate planning for dental health services and to progress strategies to continue the reduction in tooth loss, it is important to identify the factors that result in such loss. therefore the aim of the study is to investigate the major cause for tooth extraction. Objective: to examine whether the major reason for tooth extraction is dental caries or periodontal disease. Materials and Methods: The study is carried out among the dental practitioners in our district. A questionnaire containing 10 items was distributed to the dental practitioners, which included age, gender, no of teeth indicated for extraction, the reason for extraction, and the periodontal parameters that are involved with the extracted tooth and were requested to complete the form on every extraction they were to undertake. the study form was collected at the end of the study period and data was subjected to statistical analysis. Results: A total of 502 patients were enrolled during the study period, and a total of 1055 teeth were extracted for several reasons. we found that 51.14%extractions are due to dental caries in case of 20-30years age groups, which is more when compared to tooth loss due to periodontal diseases in this age group. whereas in case of >40years of age group periodontal diseases account for 54.11%, and dental caries accounts for only 29.11%. Showing more teeth were lost due to periodontal disease. Conclusion: therefore we concluded that, caries is the dominant reason for extraction in patients with 20-30 years of age while periodontal disease accounts for the majority of tooth extraction in patients older than 40 years.